Novel Compound Heterozygous BBS2 and Homozygous MKKS Variants Detected in Chinese Families with Bardet–Biedl Syndrome - Li Huang; Limei Sun; Zhirong Wang; Songshan Li; Chonglin Chen; Xiaoling Luo; Xiaoyan Ding (Journal of Ophthalmology)
Background. Bardet–Biedl syndrome (BBS) is a rare multisystem developmental disorder. In this study, we report the genetic causes and clinical manifestations in two Chinese families with BBS. Materials and Methods. Two families were recruited in this study. Family A was a four-generation family with four affected and 15 unaffected members participating in the study, and family B was a consanguineous family with one affected and three unaffected members participating. Whole exome sequencing was performed in the two families, followed by a multistep bioinformatics analysis. Sanger sequencing was used to verify the variants and to perform a segregation analysis. Comprehensive ocular and systemic examinations were also conducted. Results. Novel compound heterozygous variants c.235T > G (p.T79P) and c.534 + 1G > T were detected in the BBS2 gene in family A, and known homozygous variant c.748G > A (p.G250R) was detected in the MKKS gene in family B. Both families presented with retinitis pigmentosa; however, except for polydactyly, all other systemic manifestations were different. All of the affected family members in family A were overweight with a high body mass index (range from 26.5 to 41.9) and high blood pressure. Family A also presented with a delay in the onset of secondary sex characteristics and genital anomalies, while other systemic abnormalities were absent in family B. Conclusions. This study presents one family with two novel BBS2 variants, expanding the variant spectrum of BBS, and one family with a known homozygous MKKS variant. The different phenotypes seen between the families with BBS2 and MKKS variants will contribute to the literature and our overall understanding of BBS.